Підвищення ефективності глибокого свердління спіральними свердлами при обробці деталей з матеріалу сталь 40 - Васильєв, Є. А.; Попов, С. В.; Васильєв, А. В. (НТУ "ХПІ", 2016)
У статті представлені результати теоретичних й експериментальних досліджень процесу глибокого свердління спіральним свердлом. Отримана математична модель залежності осьового зусилля від глибини різання, діаметру свердла, подачі і швидкості різання. Наведені рекомендації для підвищення продуктивності процесу свердління.

This paper deals with the obtainment of process mathematical model of deep-hole twist drilling. In this article we have aimed to describe the processes that occur during deep-hole drilling depending on the depth of cut, drill diameter, feed and cutting velocity. There have been provided recommendations to improve the performance of the drilling process. Deep-hole drilling process isa time-consuming working operation, especially in machining viscous materials, and in the system “machining station – device – tool – component part” in deep-hole drilling process the tool – the twist drill – works under the worst and the heaviest conditions. Accordingly, the enhancement of tool life will lead to increasein productivity of the cutting process, to decrease of energy requirement and the number of the utilizable tools. The knowledge of the process mathematical model of deep-hole twist drilling gives an insight into better understanding of the influence quantity of some or another value on the overall effectiveness of the process and allows to elaborate recommendations for ranging.
Efficiency upgrading of twist bit deep-hole drilling in machining of steel-40 parts
Keywords: глибоке свердління; механізм подач; стійкість; жорсткість; ефективність; математичне моделювання; deep-hole drilling; feed gearing; toughness; efficiency; mathematic simulation